Digital Divide in Cybersecurity - Triplett, William J. (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
The digital gap actively determines how people obtain varying degrees of access to technological resources, educational opportunities, and job opportunities, specifically within cybersecurity. Research explores digital divide patterns in cybersecurity populations by analyzing unequal opportunities related to cybersecurity education, job opportunities, and security protection levels. This study combines demographic analytics and interview data to reveal how socioeconomic standing, racial background, gender identities, and regional locations simultaneously shape cybersecurity accessibility and workforce take-up. The data reveals systemic obstacles between low-income citizens and minority groups while closing access to awareness regarding entry into cybersecurity roles. The study ends by suggesting policy and educational outreach reforms that might eliminate digital inequalities.